2010
DOI: 10.1074/jbc.m110.109843
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Sp1 in Transcriptional Regulation of Phosphatidylethanolamine N-Methyltransferase in Liver and 3T3-L1 Adipocytes

Abstract: Phosphatidylcholine is made in all nucleated mammalian cells via the CDP-choline pathway. Another major pathway for phosphatidylcholine biosynthesis in liver is catalyzed by phosphatidylethanolamine N-methyltransferase (PEMT). We have now identified 3T3-L1 adipocytes as a cell culture model that expresses PEMT endogenously. We have found that PEMT mRNA and protein levels increased dramatically in 3T3-L1 cells upon differentiation to adipocytes. 5-Deletion analysis of the PEMT promoter-luciferase constructs sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
4
15
0
Order By: Relevance
“…High Fat Challenge Induces PEMT Expression in Adipose Tissue-Recent results have demonstrated that PEMT expression in 3T3-L1 adipocytes gradually increases in a time-dependent manner during adipocyte differentiation, starting at day 5 and reaching a maximum at day 7 (40). Consistent with these findings, Fig.…”
Section: Ld Monolayer Compared With Cellular Membranes Contains Pc supporting
confidence: 80%
See 2 more Smart Citations
“…High Fat Challenge Induces PEMT Expression in Adipose Tissue-Recent results have demonstrated that PEMT expression in 3T3-L1 adipocytes gradually increases in a time-dependent manner during adipocyte differentiation, starting at day 5 and reaching a maximum at day 7 (40). Consistent with these findings, Fig.…”
Section: Ld Monolayer Compared With Cellular Membranes Contains Pc supporting
confidence: 80%
“…7A). In line with a recent report (40), PEMT mRNA levels increased markedly between days 5 and 9 of 3T3-L1 differentiation, whereas the signal was virtually absent from undifferentiated cells (day 0). Expression of PS synthase-1 mRNA, which produces PS by exchange of choline in PC for serine (47), was unchanged at day 5 and was moderately higher at day 9.…”
Section: Regulatory Loop Between Pe-synthesizing and Pe-convertingsupporting
confidence: 77%
See 1 more Smart Citation
“…Recently, transcriptional regulation of two additional phospholipid biosynthetic genes was explored: phosphatidylethanolamine N-methyltransferase, which methylates phosphatidylethanolamine to generate phosphatidylcholine, and CTP:phosphoethanolamine cytidylyltransferase, which catalyzes the ratelimiting step of phosphatidylethanolamine synthesis via the CDP-ethanolamine pathway. Interestingly, both genes are negatively regulated by Sp1 during cell differentiation (62,63). The present studies identify PSS1 as another phospholipid biosynthetic activity that is transcriptionally regulated.…”
Section: Discussionmentioning
confidence: 74%
“…In support of this finding, the expression of Sp1 has been shown to decrease upon differentiation of 3T3-L1 preadipocytes. 33) Sp1 belongs to Sp transcription factor family with C 2 H 2 -type zinc finger and is involved in the regulation of the housekeeping genes. 34) IBMX, which is a cAMP phosphodiesterase inhibitor and one of the differentiation inducers, suppressed the expression of Sp1 by increasing the cellular cAMP level.…”
Section: )mentioning
confidence: 99%